Comparative education in Greece, as a European 'semi-periphery'. Issue 4 (2nd October 2018) - Prokou, Eleni
ABSTRACT: Comparative education was established in Greek universities in the 1980s, with the creation of pedagogical departments and two laboratories, and the publication of a journal . There was an early emphasis on education policy analysis, in terms of assumptions about the 'semi-peripherality' of Greece within Europe. Later, the emphasis shifted to what was also called 'modernisation' – framed by entry to the European Economic Community. There was an emphasis on education policies in other European countries, and the educational policy of Europe, in contrast with Greece which had not yet absorbed what was becoming 'a European discourse'. There was a continuing motif – reflections on methodology – but the changing concepts of modernisation, the more or less permanent anxiety about reforming Greek education, and the theme of education within the European Union dominated academic work in comparative education in Greece – even after 2010 and the major new economic crisis. An optimistic view is that comparative education will continue to develop in the Greek university through teaching and research. There is, however, a question to be asked about the silences within Greek comparative education.